Recovery of Transition Metal Ions from Binary Mixtures by Ion-exchange Column Chromatography using Synthesized Chelating Resin Derived from m-Cresol - A. Shah, Bhavna; V. Shah, Ajay; N. Bhandari, Bharat (Asian Journal of Chemistry, 2016)
Chelating ion-exchange resin was synthesized from oxine 8-hydroxyquinoline-formaldehyde-m-cresol. The physico-chemical properties like % moisture content, true density of resin (dres), apparent density of resin (dcol), void volume fraction, total exchange capacity, rate of exchange, interruption test, salt splitting capacity, thermal stability, resin stability, pH study for metal ions and effect of metal ion concentration on exchange capacity were measured. The resin was characterized by FT-IR, 1H-NMR spectra and TGA. The quantitative separation of metal ions from the mixture of cadmium(II)-copper(II), lead(II)-zinc(II), copper(II)-zinc(II) and nickel(II)-zinc(II) was accomplished by selective sorption on column at optimized Kd values.